Educational Verses in the Qur’anic Text: Pedagogical and Andragogy Perspectives - Wahyudi, Winarto Eka; Fakhrudiin, Ahmad Hanif; Ikmal, Hepi (Jurnal Pendidikan Progresif, 2024)
Abstrak: Educational Verses in the Qur'anic Text: Pedagogical and Andragogy Perspectives. Objective. This study investigates the educational concepts of andragogy and pedagogy within the context of the Koran, focusing on the letters of Luqman and al-Kahf. Andragogy and pedagogy are commonly associated with the age of learners, with andragogy pertaining to adult education and pedagogy to child education. The objective of this research is to analyze these two concepts as they appear in the Koranic texts. Through a literature analysis, the study identifies andragogical and pedagogical themes in Surah Luqman and Surah al-Kahf. Method. This study is literature analysis. By examining existing scholarly interpretations and conducting a detailed textual analysis of Surah Luqman and Surah al-Kahf, the study identifies andragogical and pedagogical themes within these texts. This method allows for a comprehensive understanding of the educational narratives and principles embedded in the Koran. Findings: that Surah Luqman presents a rich pedagogical narrative that underscores the importance of worship and the imperative for children to exhibit good behavior towards their parents and others. This narrative serves as a foundational lesson in morality and ethics, aligning with the principles of pedagogy which focus on guiding and nurturing young learners. On the other hand, Surah al-Kahf embodies andragogical principles, emphasizing the education of adults through discussion and critical thinking. The characters in this surah are depicted engaging in dialogues and reflective thought, which are key elements of andragogical education aimed at fostering self-directed learning and deeper understanding. Conclusion: this study highlights the presence of both pedagogical and andragogical elements in the Koran, demonstrating its comprehensive approach to education across different age groups. This research contributes to the broader field of educational studies by offering a unique perspective on the interpretation of the Koran through the lens of educational theory. Keywords: andragogy, critical discourse, pedagogy, qur’anic text.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202447